The Choice of Resin-Bound Ligand Affects the Structure and Immunogenicity of Column-Purified Human Papillomavirus Type 16 Virus-Like Particles - Kim, Hyoung Jin; Lim, Su Jeung; Kwag, Hye-Lim; Kim, Hong-Jin (PLOS ONE, 2012)
Cell growth conditions and purification methods are important in determining biopharmaceutical activity. However, in studies aimed at manufacturing virus-like particles (VLPs) for the purpose of creating a prophylactic vaccine and antigen for human papillomavirus (HPV), the effects of the presence of a resin-bound ligand during purification have never been investigated. In this study, we compared the structural integrity and immunogenicity of two kinds of VLPs derived from HPV type 16 (HPV16 VLPs): one VLP was purified by heparin chromatography (hHPV16 VLP) and the other by cation-exchange chromatography (cHPV16 VLP). The reactivity of anti-HPV16 neutralizing monoclonal antibodies (H16.V5 and H16.E70) towards hHPV16 VLP were significantly higher than the observed cHPV16 VLP reactivities, implying that hHPV16 VLP possesses a greater number of neutralizing epitopes and has a greater potential to elicit anti-HPV16 neutralizing antibodies. After the application of heparin chromatography, HPV16 VLP has a higher affinity for H16.V5 and H16.E70. This result indicates that heparin chromatography is valuable in selecting functional HPV16 VLPs. In regard to VLP immunogenicity, the anti-HPV16 L1 IgG and neutralizing antibody levels elicited by immunizations of mice with hHPV16 VLPs were higher than those elicited by cHPV16 VLP with and without adjuvant. Therefore, the ability of hHPV16 VLP to elicit humoral immune responses was superior to that of cHPV16 VLP. We conclude that the specific chromatographic technique employed for the purification of HPV16 VLPs is an important factor in determining the structural characteristics and immunogenicity of column-purified VLPs.